Analisis Manajemen Promosi Ritel pada Toko SRC Satria dalam Meningkatkan Minat Beli dan Loyalitas Konsumen (Jurnal Manajemen Kreatif dan Inovasi, 2026)
The development of the retail sector, especially with the rise of modern retail and franchise minimarkets, encourages small-scale retail businesses to adapt through effective marketing strategies. This study aims to analyze the implementation of retail promotion management at Toko SRC Satria and its role in increasing consumer buying interest and loyalty. Using a qualitative approach with a descriptive method, data was collected through observations, in-depth interviews, and documentation with the store owner and consumers. The results show that Toko SRC Satria has implemented a planned retail promotion management strategy, even on a small scale, including neat product arrangement, attractive display usage, discounts, bundled offers, and intense direct communication between the store owner and consumers. The application of these strategies creates a comfortable shopping experience and increases consumer interest in making purchases. This study also shows that retail promotion management contributes to increasing buying interest, as seen in the stable frequency of visits and the tendency for repeat purchases. A personal approach and friendly service are important factors in building consumer loyalty. The implications of this study suggest that simple yet targeted retail promotion management can enhance competitiveness and support the sustainability of businesses amid fierce competition.